2000
DOI: 10.1080/02724930091995
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and radiological features of tuberculosis in adolescents

Abstract: This retrospective review of clinical records and chest radiographs (CR) of adolescents aged 10-18 years was designed to determine age and sex differences in the clinical and radiological features of adolescent tuberculosis (TB). Records of adolescents who were admitted to Brooklyn Hospital for Chest Diseases (BCH) or who were treated at local authority health clinics were screened. Data from 324 adolescents (male:female ratio 1:1.2) were studied. Intra-thoracic lesions were present on CR in 306 (94%). Primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 7 publications
5
31
0
1
Order By: Relevance
“…Since this age group has extensive social combination and assembly in schools and colleges, these patients are able to transmit the TB infection to others. Furthermore, the adolescent age group is specific for physiological changes which occur during puberty and play an important role in pulmonary TB disease (17). This can illustrate the higher risk to get TB after recent TB infection and re-infection among adolescent age group compared with children.…”
Section: Discussionmentioning
confidence: 86%
“…Since this age group has extensive social combination and assembly in schools and colleges, these patients are able to transmit the TB infection to others. Furthermore, the adolescent age group is specific for physiological changes which occur during puberty and play an important role in pulmonary TB disease (17). This can illustrate the higher risk to get TB after recent TB infection and re-infection among adolescent age group compared with children.…”
Section: Discussionmentioning
confidence: 86%
“…5 In mid-childhood, mediastinal lymph 6 7 node disease predominates; adult-type disease with pleural effusions and cavitation typically emerges during adolescence. 4,6 The confirmation of TB in children is challenging due to the 8 paucibacillary nature of the disease, challenges in specimen collection and the wide observed 9 disease spectrum. In addition to informing clinical care, the use of standard case definitions is 10 important to enable the adequate comparison of children in clinical research, where the yield of 11 diagnostic tests, response to treatment, and the efficacy of new drugs or regimen and vaccines are 12 13 evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of pulmonary TB in adolescents in Brazil, it was detected that there was a slight predominance of cavitary pulmonary TB in adolescent females compared with adolescent males although the difference was not statistically significant (9). It has been shown that cavitary pulmonary TB is more frequently seen in females than males between the ages of 14 -17 years (8).…”
Section: Discussionmentioning
confidence: 99%